Effectiveness of Health Promotion on the Knowledge and Attitudes of Mothers of Toddlers regarding Stunting at the Siatasbarita Community Health Center, Siatasbarita District in 2022 - Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Stunting is a chronic nutritional problem that can cause growth disorders in children. Health promotion is a very necessary effort to reduce stunting rates. Health promotion is provided to the community so people know, want and can maintain and improve their health. One strategy is advocacy, namely providing information through counselling in collaboration with toddler integrated healthcare centre. This research aims to determine the effectiveness of health promotion on mothers' knowledge and attitudes about stunting. This type of research is quasi-experimental with a pretest and posttest group design. The research was conducted from June to November 2022 in Sitompul Village and Lumban Siagian Jae Village. The population was mothers who had stunted toddlers in Sitompul Village and Lumban Siagian Jae Village, the sample was 40 mothers who came to the integrated healthcare center. The sampling technique was Accidental Sampling, namely several mothers who came to the integrated healthcare center in August. and September 2022. data collection using a questionnaire. Data analysis using bivariate analysis using the Wilcoxon test. The results showed that there was an effect of counselling on knowledge (p-value=0.000) < 0.05, and there was no effect of counselling on mothers' attitudes about stunting (p-value=0.317) > 0.05 at Siatas Barita Health Center, Siatas Barita District. Counselling effectively increases knowledge but does not improve mothers' attitudes about stunting. It is hoped that health workers will improve their approach to mothers to increase their knowledge and attitudes about stunting to prevent and treat stunting in children. Keywords: Attitude, Effectiveness, Health Promotion, Knowledge, Stunting